Evaluation of Tissue and Serum Expression Levels of Lactate Dehydrogenase Isoenzymes in Patients with Head and Neck Squamous Cell Carcinoma - Mohtasham, Nooshin; Ayatollahi, Hossein; Saghravanian, Nasrollah; Zare, Reza; Shakeri, Mohammad-Taghi; Sahebkar, Amirhossein; Mohajertehran, Farnaz (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Head and Neck Squamous Cell Carcinoma (HNSCC) is a common malignancy that is associated with high morbidity and mortality all over the world. We explored the role of mRNA expression of both subunits of LDH in the early diagnosis of HNSCC. Materials and Methods: This was a case-control study on 62 healthy individuals and 62 patients with HNSCC. The expression of LDH in tumors and healthy tissue margins, and in the serum of both HNSCC patients and healthy individuals was evaluated using a quantitative real-time PCR method. Analysis of LDH-A and LDH-B expression and sensitivity-specificity analysis were carried out using SPSS software. Results: mRNA expression levels of LDH-A (4.18±1.29) and LDH-B (2.85±1.07) isoenzymes in tumor tissues were significantly higher than the expressions in the corresponding healthy tissue margins (1.85±0.56 and 1.61±0.56 for LDH-A and LDH-B, respectively). A comparison of LDH-B expression between histological grade I tumor tissue (2.74±0.19) and marginal tissue (1.62±0.90) showed a significant difference (P=0.016). Patients with a positive history of alcohol consumption and cigarette smoking had significantly higher mRNA expression of LDH-A (P=0.024) and LDH-B (P=0.03) in the marginal tissue and blood, respectively. The highest sensitivity and specificity values pertained to the mRNA expression of LDH-A (90.9%) and LDH-B (85.5%) in the blood. Conclusion: This is the first study reporting LDH gene expression as a biomarker in blood and tumoral tissue of HNSCC patients. Given the highest sensitivity and specificity values for LDH-A and LDH-B in blood, we recommend the simultaneous evaluation of both LDH isoenzymes in blood samples as a potential diagnostic method.
Keywords: gene expression